The healing effect of hydrogen-rich water on acute radiation-induced skin injury in rats. (27th September 2018) - Zhou, Ping; Lin, Bing; Wang, Peng; Pan, Tao; Wang, Shun; Chen, Weisi; Cheng, Shaowen; Liu, Sha
Abstract: This study aimed to determine the healing effect of hydrogen-rich water (HRW) on radiotherapy-induced skin injury. Rats were irradiated with a 6 MeV electron beam from a Varian linear accelerator. After skin wound formation, rats were individually administrated with distilled water, HRW (1.0 ppm) or HRW (2.0 ppm). We measured the healing time and observed the healing rate of the wounded surface. After irradiation, the malondialdehyde (MDA) content and the superoxide dismutase (SOD) activity in the wounded tissues were evaluated, as determined using an MDA and SOD assay kit. Interleukin-6 (IL-6) and epidermal growth factor (EGF) levels were assessed by enzyme-linked immunosorbent assay (ELISA). Models of skin damage were successfully established using a 44 Gy electronic beam. The healing time was shortened in the two HRW-treated groups ( P < 0.05). Furthermore, interventions of HRW resulted in a marked reduction in the MDA ( P < 0.05) and IL-6 levels ( P < 0.01). Additionally, the SOD activity in the two HRW-treated groups was higher than that in the distilled water group at the end of the 1st, 2nd and 3rd weeks ( P < 0.001). The EGF level was also significantly increased at the end of the 1st and 2nd weeks ( P < 0.05). Compared with the HRW (1.0 ppm) group, the healing rate was higher and the healing time was reduced in the HRW (2.0 ppm) group. A significant decrease was observed in the IL-6 level at the end of the 1st, 3rd and 4th weeks ( P < 0.05) and in the EGF content at the end of the 1 week after the HRW administration ( P < 0.01). Collectively, our data indicate that HRW accelerates wound healing of radiation-induced skin lesions through anti-oxidative and anti-inflammatory effects, suggesting that HRW has a healing effect on acute radiation-mediated skin injury, and that this is dependent on the concentration of the hydrogen.